2009
DOI: 10.1002/ajmg.a.32877
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complex 7q21.3 rearrangement in a patient with bilateral split‐foot malformation and hearing loss

Abstract: We report on complex rearrangements of the 7q21.3 region in a female patient with bilateral split-foot malformation and hearing loss. G-banding karyotype was 46,XX,t(7;15)(q21;q15),t(9;14)(q21;q11.2)dn. By fluorescence, in situ hybridization (FISH), Southern hybridization, and inverse PCR, the 7q21.3 translocation breakpoint was determined at the nucleotide level. The breakpoint did not disrupt any genes, but was mapped to 38-kb telomeric to the DSS1 gene, and 258- and 272-kb centromeric to the DLX6 and DLX5 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…In addition, disruption of both Dlx5 and Dlx6 also resulted in limb malformations that phenocopied Split hand/foot and mouth syndrome (SHFM) in humans (Robledo et al, 2002). The Dlx5 and 6 genes are located in the SHFM type 1 locus on human 7q21, and approximately 35% of those with SHFM1 also have sensorineural, or mixed hearing loss (Elliott and Evans, 2006; Saitsu et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…In addition, disruption of both Dlx5 and Dlx6 also resulted in limb malformations that phenocopied Split hand/foot and mouth syndrome (SHFM) in humans (Robledo et al, 2002). The Dlx5 and 6 genes are located in the SHFM type 1 locus on human 7q21, and approximately 35% of those with SHFM1 also have sensorineural, or mixed hearing loss (Elliott and Evans, 2006; Saitsu et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…This model is in agreement with recent reports on genomic aberrations in 7q21 that were associated with SHFM1. In one report, a human breakpoint located at 38 kb telomeric to DSS1 and at 258 kb centromeric to DLX6 is associated with SHFM and hearing loss phenotype (Figure S5) [82]. This breakpoint leaves the SHFM1-BS1 association with DSS1 intact, but disconnects it from DLX5 and DLX6 .…”
Section: Discussionmentioning
confidence: 99%
“…All had hearing loss due to abnormalities of the inner ear but none showed limb abnormalities. Saitsu et al (2009) reported a complex rearrangement in a patient with bilateral split-foot malformation and hearing loss. This well-characterized rearrangement detected a chromosomal 7q21.3 break, mapped to 258 and 272 kb centromeric to the DLX6 and DLX5, respectively, in addition to a microdeletion of 806 kb located 750 kb telomeric to the 7q21.3 breakpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Besides TP63 located on chromosome 3q27, five other loci have been considered in relation to syndromic and non-syndromic SHFM: SHFM1 on chromosome 7q21, SHFM2 on Xq26, SHFM3 on 10q24, SHFM5 on 2q31 and SHFM6 on 12q13 (for review see Saitsu et al, 2009). SHFM1 is associated with deletions of variable extent on chromosome 7q21, minimally including the DSS1 gene and the distallessrelated homeogenes DLX5 and DLX6 (Crackower et al, 1996;Scherer et al, 1994aScherer et al, , 1994b.…”
Section: Introductionmentioning
confidence: 99%